Assessing the Extent of Electronic Procurement Adoption Challenges in the Public Sector of Ghana - Salifu, Zaruk Narsam; Nangpiire, Clement; Dawdi, Abdul-Aziz; Yussif, Fatawu (International Journal of Economics and Financial Issues, 2023)
Electronic procurement implementation challenges are highly noticed in many African countries including Ghana despite the enormous benefit seen in nations that have adopted e-procurement. This study is quantitative by design and seeks to examine the extent of challenges that affect the implementation of electronic procurement. Knowledge of the extent of the challenges is essential to policy implementers to identify the significant challenges and the less significant challenges and prioritize their spending thereof due to the limited availability of resources. A total of three hundred and thirty-three (333) respondents’ views were considered. The one-way analysis of variance is adopted to analyze the extent of e-procurement implementation challenges in public institutions and coefficients were reported at 95% CI and 5% significance level using (SPSS v20.0). The overall finding indicates that ICT contributes more to the implementation challenges of e-procurement than the institutional, employee, and supplier factors. Based on the finding, we recommend that regular training or seminars should be organized to equip employees with the necessary knowledge about e-procurement processes and procedures; ICT infrastructure needs of the public institutions must be given priority to ensure the smooth adoption of electronic procurement.